REVISITING THE MAUSOLEUM AT HERODIUM: IS IT HEROD'S TOMB?. (December 2015) - Patrich, Joseph; Arubas, Benjamin
Abstract : An attentive examination of the impressive finds of the mausoleum uncovered in 2007 in Herodium has demonstrated that these are not in accord with the characteristics of Herodian architecture as postulated by the late Prof. Ehud Netzer. The following four arguments show that this monument, which was indeed built by Herod, did not serve as his eternal resting place:   Its moderate dimensions.   The absence of an appropriate gateway to the burial ground, and an adequate assembly space around the tomb.   A stratigraphic argument: The stairway leading up to the palace-fortress on the hilltop leaves the mausoleum 'in its shade', being also overlaid on top of the single irrigation pool that served the small garden that had surrounded the tomb.   The absence of any correspondence between the axis of symmetry of the mausoleum, and that of Greater Herodium, indicating that these two were entirely different building projects. Two alternative proposals are presented for the possible locations of the tomb, which might have disappeared.